Fermentation of Sugarcane Biomass Hemicellulosic Hydrolysate by Yeast-Producer of Xylitol and Ethanol Isolated from the Atlantic Forest and the Brazilian Amazon Forest - Souza, Jonas P. [UNESP]; Fogarin, Henrique M. [UNESP]; Almeida, Sâmilla G. C. [UNESP]; Santos, Bianca C. S. [UNESP]; Silva, Débora D. V. [UNESP]; Dussán, Kelly J. [UNESP] (Springer Nature, 2025)
Abstract: In this study, the fermentative performances of the new yeast species Spathaspora boniae (UFMG-CM-Y306) and Spathaspora brasiliensis (UFMG-HMD19.3), isolated from decaying wood in Brazilian ecosystems, were investigated for the first time in sugarcane biomass hemicellulosic hydrolysate (mixture of bagasse and sugarcane straw). The best condition for supplementing the hydrolysate with different nitrogen sources (urea, yeast extract, peptone, and ammonium sulfate) was evaluated using a face-centered central composite design. Both, S. boniae and S. brasiliensis were able to assimilate sugars and produce xylitol as the main product and ethanol as a by-product of fermentation. S. boniae consumed 97.05% sugars and was able to produce xylitol 10.74 g L−1 (YP/S = 0.437 gg−1, QP = 0.149 gL−1 h−1) and ethanol 3.86 g L−1 (YP/S = 0.157 gg−1, QP = 0.054 gL−1 h−1) in non-detoxified hydrolysate, showing resistance to toxic compounds. On the contrary, S. brasiliensis required the detoxification step of sugarcane biomass hemicellulosic hydrolysate, producing xylitol 10.62 g L−1 (YP/S = 0.475 gg−1, QP = 0.147 gL−1 h−1) and ethanol 1.4 g L−1 (YP/S = 0.054 gg−1, QP = 0.019 gL−1 h−1). Thus, the results of the optimization of nitrogen sources for the supplementation of hemicellulosic hydrolysate of sugarcane biomass to sugar are significant in aspects such as exploiting the biodiversity of Brazilian biomes and supporting the process of expansion of biorefineries. Statement of Novelty: The fermentative capacity of the xylose-fermenting yeasts Spathaspora boniae and Spathaspora brasiliensis was evaluated using the hemicellulosic hydrolysate produced from a mixture of bagasse and sugarcane straw. Unlike the yeast Spathaspora brasiliensis, which requires detoxified hydrolysate to produce xylitol, the yeast Spathaspora boniae can produce xylitol in hydrolysate without detoxification. Urea, yeast extract, peptone, and ammonium sulfate were used as nitrogen sources to optimize the fermentation process with xylitol as the goal. Furthermore, since there is relatively little literature published on the evaluation of the fermentative capacity of these yeast species in the sugarcane biomass hemicellulosic substrate, the results of this study have important implications for the use of these yeasts in biorefineries. Graphic Abstract: (Figure presented.)
Keywords: Lignocellulose; Nitrogen sources; Optimization; Spathaspora boniae; Spathaspora brasiliensis; Xylose